Breed Distribution of SOD1 Alleles Previously Associated with Canine Degenerative Myelopathy. (13th February 2014) - Zeng, R.; Coates, J.R.; Johnson, G.C.; Hansen, L.; Awano, T.; Kolicheski, A.; Ivansson, E.; Perloski, M.; Lindblad‐Toh, K.; O'Brien, D.P.; Guo, J.; Katz, M.L.; et al.
<x xml:space="preserve">Abstract</x> Background Previous reports associated 2 mutant SOD1 alleles (SOD1:c.118A and SOD1:c.52T) with degenerative myelopathy in 6 canine breeds. The distribution of these alleles in other breeds has not been reported. Objective To describe the distribution of SOD1:c.118A and SOD1:c.52T in 222 breeds. Animals DNA from 33, 747 dogs was genotyped at SOD1:c.118, SOD1:c.52, or both. Spinal cord sections from 249 of these dogs were examined. Methods Retrospective analysis of 35, 359 previously determined genotypes at SOD1:c.118G>A or SOD1:c.52A>T and prospective survey to update the clinical status of a subset of dogs from which samples were obtained with a relatively low ascertainment bias. Results The SOD1:c.118A allele was found in cross‐bred dogs and in 124 different canine breeds whereas the SOD1:c.52T allele was only found in Bernese Mountain Dogs. Most of the dogs with histopathologically confirmed degenerative myelopathy were SOD1:c.118A homozygotes, but 8 dogs with histopathologically confirmed degenerative myelopathy were SOD1:c.118A/G heterozygotes and had no other sequence variants in their SOD1 amino acid coding regions. The updated clinical conditions of dogs from which samples were obtained with a relatively low ascertainment bias suggest that SOD1:c.118A homozygotes are at a much higher risk of developing degenerative myelopathy than are SOD1:c.118A/G heterozygotes. Conclusions and Clinical Importance We conclude that the SOD1:c.118A allele is widespread and common among privately owned dogs whereas the SOD1:c.52T allele is rare and appears to be limited to Bernese Mountain Dogs. We also conclude that breeding to avoid the production of SOD1:c.118A homozygotes is a rational strategy.